Protecting the future: Childhood vaccination as a prevention and health promotion action in primary care - Lima, Pâmela Lorrane Sousa; Silva, Raylanna Oliveira; Pessoa, Nágila Anne da Silva; Fernandes, Hayla Bertrine Guedes Barbosa; Cruz, Ana Vitória Correia da; Prates, Carlos Henrique Nonato; Fraga, Vanessa Rodrigues Silva (Seven Editora, 2024)
Childhood vaccination, essential for global public health, plays a crucial role in preventing diseases and reducing morbidity and associated health costs. Despite scientific advances, challenges persist, such as misinformation and lack of access to health services. The COVID-19 pandemic has accentuated the drop in vaccination coverage rates in Brazil, requiring specific actions. Thus, this intervention project aimed to address critical issues related to childhood immunization, focusing on informing and sensitizing children, parents and guardians about the importance of vaccines, presenting the Basic Vaccination Schedule and highlighting the relevance in disease prevention. The project, implemented in the second half of 2023, contributed to raising awareness among the population about the importance of vaccination, especially pregnant women, the elderly, and children. The dynamics included theoretical presentations, group debates, learning dynamics and distribution of gifts and informative posters. The project reinforced that childhood vaccination is crucial to protect children against diseases and their potential sequelae. By highlighting the understanding of parents or guardians about the importance of vaccination, the benefits for children's health, preventing infectious diseases and potential complications, were emphasized. Therefore, the continuous need to develop new health actions aimed at vaccination to mitigate these challenges and ensure the protection of public health is emphasized. DOI: https://doi.org/10.56238/sevened2024.007-032